REPEATED FREEZE-THAW CYCLES BUT NOT SHORT-TERM STORAGE OF FECAL EXTRACTS AT AMBIENT TEMPERATURE INFLUENCE THE STABILITY OF STEROID METABOLITE LEVELS IN CRESTED MACAQUES - Gholib Gholib; Muhammad Agil; Iman Supriatna; Bambang Purwantara; Michael Heistermann; Antje Engelhardt (Jurnal Kedokteran Hewan, 2017)
The objective of this study was to examine the effects of repeated freeze-thaw cycles and short-term storage of fecal extracts at ambient temperature on the stability of fecal glucocorticoid (fGCM) and estrogen metabolite (fEM) levels from crested macaques.In total 100 aliquots of fecal extracts from fecal samples collected from female crested macaques (Macaca nigra) living at the Tangkoko-Batuangus Nature Reserve, North Sulawesi were used. We performed two different experiments: (1) An experiment to investigate if levels of fGCM and fEM measured from fecal extracts that were exposed to two, four, six and eight repeated freeze-thaw cycles (test groups) differ to control samples (i.e. fecal extracts always stored frozen); (2) An experiment to evaluate whether storing fecal extracts at ambient temperature for two, four, six, and eight days (test groups)affects the levels of fGCM and fEM compared to the control group (i.e. fecal extracts frozen immediately).Results showed that hormone levels were significantly increased (P0.05) after four freeze-thaw cycles for fGCM and after eight freeze-thaw cycles for fEM. By contrast, there was no significant difference (P0.05) in levels of fGCM and fEM between the test groups and the control group in fecal extracts stored at ambient temperature. In conclusion, our data show that more than two and six repeated freeze-thaw cycles should be avoided when measuring fGCM and fEM in crested macaque fecal extracts, respectively. We also demonstrate that storing fecal extracts at ambient temperature is possible for at least 8 days without taking a risk of affecting the stability of fGCM and fEM levels.